RECORD OF Smicromorpha, (HYMENOPTERA: CHALCIDIDAE: SMICROMORPHINAE) POSSIBLE PARASITOIDS OF WEAVER ANTS, FROM HALMAHERA, THE NORTH MOLUCCAS - Rosichon Ubaidillah; Jun-ichi Kojima (BRIN Publishing (Penerbit BRIN), 2004)
-